2019
DOI: 10.1089/chi.2018.0233
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Perpetration and Victimization among Adolescents with Overweight and Obesity in a Nationally Representative Sample

Abstract: Background: Adolescents with obesity are more likely to experience bullying in comparison to their healthy weight peers. However, it is unclear whether adolescents with obesity are more likely to perpetuate bullying or be both, a bully perpetrator and a bully victim. The purpose of this analysis was to examine differences in bully perpetration, victimization, and both (perpetration and victimization) by BMI classification in a nationally representative sample of adolescents. Methods: Analyses included 31,770 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
3
19
1
Order By: Relevance
“…This supports prior research showing children with OW/OB display more externalizing behaviour and conduct problems, which may be linked to bullying behaviour and maladaptive coping skills for weight-related stigma and discrimination. 7,26 Lastly, the lack of association between ADHD and OW/OB is consistent with other studies showing mixed evidence for this relationship in youth. 7 Conversely, the association between underweight status and ADHD in the present sample aligns with another study that found underweight or healthy weight youth had higher rates of ADHD compared to those with OW/OB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports prior research showing children with OW/OB display more externalizing behaviour and conduct problems, which may be linked to bullying behaviour and maladaptive coping skills for weight-related stigma and discrimination. 7,26 Lastly, the lack of association between ADHD and OW/OB is consistent with other studies showing mixed evidence for this relationship in youth. 7 Conversely, the association between underweight status and ADHD in the present sample aligns with another study that found underweight or healthy weight youth had higher rates of ADHD compared to those with OW/OB.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, children with obesity were 30% more likely to have an ODD diagnosis compared to healthy weight children. This supports prior research showing children with OW/OB display more externalizing behaviour and conduct problems, which may be linked to bullying behaviour and maladaptive coping skills for weight‐related stigma and discrimination 7,26 . Lastly, the lack of association between ADHD and OW/OB is consistent with other studies showing mixed evidence for this relationship in youth 7 .…”
Section: Discussionsupporting
confidence: 89%
“…Obese adolescents were more susceptible to being made fun of how their body or face looked, which is consistent with a previous study. Adolescents who were underweight and overweight or obese had significantly greater odds than their healthy-weight peers of being victims of bullying (Rupp and McCoy, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Boys are more likely to be bullied physically, while girls are more often bullied verbally (Craig et al ., 2009 ). Additionally, adolescents who are underweight, overweight or obese have significantly greater odds than their healthy-weight peers of being the victims of bullying (Rupp and McCoy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' difficulty making friends was measured with a single question: “Compared to other children his or her age, how much difficulty does this child have making or keeping friends?” This item has been used to measure adolescents' friendship difficulties in other studies (Hilton et al, 2019; Rupp & McCoy, 2019). The item was rated on a three‐point scale: no difficulty (1), a little difficulty (2) , and a lot of difficulties (3) .…”
Section: Methodsmentioning
confidence: 99%